IMPLEMENTASI TEKNOLOGI AUGMENTED REALITY SEBAGAI MEDIA INFORMASI SARANA DAN PRASARANA PADA SDN 095212 N. BAYU, NEGERI BAYU MUSLIMIN, KEC. TAPIAN DOLOK, KAB. SIMALUNGUN - Aulia Fasya Ardana (PT. Hasba Edukasi Mandiri, 2025)
This study discusses the implementation of Augmented Reality (AR) technology as an information medium for facilities and infrastructure at SDN 095212 N. Bayu, Negeri Bayu Muslimin, Tapian Dolok District, Simalungun Regency. So far, the delivery of information about school facilities has been done conventionally, which makes it less interactive and unable to capture the attention of users, especially students and the community. By utilizing AR, information about the facilities and infrastructure can be presented in a more attractive and easily understandable form. The methods used in this study include the stages of needs analysis, system design, development of a mobile-based AR application, and functionality testing of the application. This AR application works by utilizing a marker in the form of a QR code placed on the school map. When scanned with a smartphone camera, it displays information in the form of text, images, or videos related to a room or school facility. The results of the study show that the implementation of AR technology can improve the effectiveness of information delivery, provide an interactive experience for users, and support innovation in the use of digital technology n elementary school environments. Therefore, this application can become an alternative, educational, and engaging information medium that supports the school’s efforts in promoting its facilities and infrastructure.